Indonesian Millennial Financial Behaviour: The Role of Financial Literacy in Intention to Use Fintech Lending - Abadi, M. Kurnia Rahman; Saida, Umi (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The significance of financial behaviour among millennials, particularly concerning fintech lending, is important. Fintech lending is a complex subject that is increasingly being studied. However, it also provides a solution for quick and easy funds. This study proposes to notice the financial behaviour of millennials by looking at their financial literacy and how it affects their plan to use fintech lending. The study practices a quantitative research approach and gathered data from 359 respondents through purposive random sampling. Structural equation modelling was used to test the hypotheses. The study found that the variables of the theory of planned behaviour do not directly affect the intention to use fintech, on the other hand, financial literacy has a significant influence. The consequences of this study are useful for investors, financial institutions, and government officials since it emphasises the necessity of knowing millennials' financial behaviours. These behaviours can impact their product choices, as seen in their susceptibility to the FOMO syndrome